Intra- and intercellular signaling pathways associated with drug-induced cardiac pathophysiology. (August 2021) - Guo, Fei; Hall, Andrew R.; Tape, Christopher J.; Ling, Stephanie; Pointon, Amy
Abstract : Cardiac physiology and homeostasis are maintained by the interaction of multiple cell types, via both intra- and intercellular signaling pathways. Perturbations in these signaling pathways induced by oncology therapies can reduce cardiac function, ultimately leading to heart failure. As cancer survival increases, related cardiovascular complications are becoming increasingly prevalent, thus identifying the perturbations and cell signaling drivers of cardiotoxicity is increasingly important. Here, we discuss the homotypic and heterotypic cellular interactions that form the basis of intra- and intercellular cardiac signaling pathways, and how oncological agents disrupt these pathways, leading to heart failure. We also highlight the emerging systems biology techniques that can be applied, enabling a deeper understanding of the intra- and intercellular signaling pathways across multiple cell types associated with cardiovascular toxicity. Highlights: Intra- and intercellular signaling pathways are both important for cardiac physiology and functions, and interplay together to form an intricate 'network' of signaling with cardiac multicellularity at the system level. Cardiovascular toxicity can be caused not only by disrupted intracellular signaling pathway from a singular type of cardiac cells, but also by perturbing intercellular signaling between different cardiac cell types. Novel system biology techniques enable us to better understanding intra- and intercellular signaling pathways offering an opportunity to better understand cardiovascular toxicity.